Five new records of aroids for Bangladesh - Ara, Hosne; Hassan, Md. Abul (Bangladesh Journal of Plant Taxonomy, 2012)
The paper deals with five species of the family Araceae which are new records for Bangladesh, viz. Amorphophallus excentricus Hett., A. krausei Engl., Colocasia virosa Kunth, Steudnera gagei Krause and Xanthosoma undipes (K. Koch) K. Koch. An updated nomenclature, important synonyms, description, phenology, ecology, specimen citation and geographical distribution are provided for each species. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10937 Bangladesh J. Plant Taxon. 19(1): 17-23, 2012 (June)